Error 404, farmer not found: Why agricultural information services must consider how smallholders use their phones - Steinke, Jonathan; Ortiz Crespo, Berta; Bunn, Christian; Etten, Jacob van; Jimenez, Daniel; Tam Thi Le; Manners, Rhys; Muller, Anna; Phuong Minh Nguyen; Ogunsamni, Thompson; Schumann, Charlotte; Simiyu, Maryfaith; et al. (2024)
Numerous barriers hinder mobile information services in delivering information effectively to smallholder farmers. Many of these barriers can be explained by farmers’ habits in using their phones. Therefore, carefully considering how exactly farmers use their phones in specific local context is crucial to mitigate behavior-related barriers. We describe 18 potential behavioral barriers that should be checked before implementing mobile information services for smallholder agriculture.